Wither the Bumiputera Identity of Universiti Teknologi Mara (UiTM)? - Mohd. Nazim Ganti Shaari, (Kajian Malaysia, 2011)
Successive Malay leaders have defended Universiti Teknologi MARA (UiTM) as a means of ensuring the survival of the Malays and the bumiputera in Malaysia. It is impossible to deny that the contributions of UiTM have been enjoyed by all sectors of society; however, as an institutional catalyst and symbol of Malay leadership in Malaysia, its constitutional existence has been called into question in light of the 2008 general elections. This article examines the constitutional existence of UiTM with a primary objective of determining whether it has a constitutionally entrenched bumiputera identity. Possible legal hurdles to its constitutional existence, such as the right to equality and the presumably enshrined bumiputera identity, are examined with reference to similar arguments in India.